CHARACTERISTICS OF FEMALE LEADERS IN PROMOTING ESG PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Angelia, Lisa; Yanti, Yanti (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study aims to identify and analyze the unique characteristics of female leaders that contribute to the enhancement of Environmental, Social, and Governance (ESG) performance within firms. Additionally, it seeks to synthesize and critically review existing literature on the topic, examining theoretical frameworks, research themes, methodologies, and settings. Employing a systematic literature review guided by the SPAR-4-SLR protocol, the study utilizes both bibliometric and content analysis techniques. Data were gathered using the Publish or Perish software and visualized through VOSviewer, resulting in a comprehensive review of 52 relevant articles. The findings suggest that female board members exhibit distinct attributes compared to their male counterparts, which can positively impact the implementation of ESG practices. However, many studies emphasize the need for a minimum representation threshold to ensure the effectiveness of women’s participation in boardroom decision-making. The study recommends that both corporate entities and policymakers adopt gender diversity policies to foster more active involvement of female leaders in ESG-related governance. The selection of this research topic addresses a critical gap, recognizing the significant potential of women leaders in promoting balanced and comprehensive decision-making, particularly in relation to ESG considerations. Ultimately, the study maps the current landscape of research on female executive roles and board gender diversity, highlighting trends across theoretical, methodological, and contextual dimensions.